a THE CONCEPT OF JUSTICE AND TOLERANCE IN THE QUR'AN TO ACHIEVE HARMONY AMONG RELIGIOUS COMMUNITIES - Syarifaturrahmatullah Syarifaturrahmatullah; Nasrulloh; Syatria Adymas Pranajaya (Al-Fath, 2023)
The low level of tolerance often becomes a cause of conflicts between ethnic and tribal groups, especially among religious followers. This is due to a need for a more adequate understanding of the principles of tolerance in Islam, the presence of religious extremism, and injustice. The Qur'an emphasizes the concepts of justice and tolerance as the foundation for creating harmony among religious communities. This research aims to carefully explore the verses of the Qur'an related to justice and tolerance, mapping out clearly how the concepts of justice and tolerance are defined in the Qur'an and how justice and tolerance can serve as the foundation for the harmony of religious communities. The researcher utilizes a qualitative approach through library research, with research sources including the Qur'an, literary works, and scholarly writings. The study's results indicate that justice is a balance, equality, non-discriminatory, and a straight path that does not contradict the decrees of Allah. Meanwhile, tolerance is an attitude that refers to the principles of equality, justice, and mutual respect among religious communities without having to adopt the beliefs of other religions. Establishing justice and a mutual respect attitude among communities and religious followers, wrapped in open dialogue among religious communities, is the foundation for achieving harmony.